PEMANFAATAN MEDIA INTERAKTIF iSPRING DALAM PENINGKATAN LITERASI DIGITAL SISWA SD NEGERI JATI - Sayid Husein De San Wardhani; Fera Dwidarti; badri atul Fikriyah (STKIP Subang, 2025)
In an effort to improve the digital literacy skills of participants who grew up in the current era of globalization. And added with the onslaught of technological developments which not only have positive impacts but also negative impacts. Therefore, it is very important to align education with technological developments wisely. This research aims to utilize iSpring interactive media to increase digital literacy. The method used in this research is a qualitative approach with data collection techniques using a library study approach or what could be called library research, in which the author collects various references regarding the use of iSpring interactive media in students' digital literacy through journals, articles and other sources. And the methods used in this service are direct mentoring and interviews. From this research, research shows that this activity succeeded in increasing students' interest in using iSpring media in digital literacy.